Customary Law and Islamic Family Law in Resolving Out of Wedlock Pregnancy: A Socio Legal Study - Luthfia Aunie Cahyandari; Widiya Yul; Faizin Faizin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Out-of-wedlock pregnancy presents a complex socio-legal challenge within Indonesia’s plural legal system. In many Muslim communities, dispute resolution extends beyond state law and Islamic family law to include living customary norms. This study examines how customary law interacts with Islamic family law in resolving out-of-wedlock pregnancy cases. Using a socio-legal field approach, data were collected through interviews, observation, and documentation in Tambak Tinggi Village, Kerinci Regency. The findings reveal that customary law operates through deliberative mechanisms emphasizing accountability, restoration of family honor, and social reintegration through customary fines and communal reconciliation rituals. Rather than competing with Islamic family law, customary law complements it by encouraging marriage, affirming male responsibility, and safeguarding women and children. This study argues that the coexistence of customary law and Islamic family law reflects a context-sensitive model of restorative justice within Indonesia’s legal pluralism. The article contributes to socio-legal scholarship by demonstrating how local normative orders remain relevant in addressing contemporary family disputes.